Evaluating national innovation systems: Key insights from the Finnish innoeval survey - Annu Kotiranta; Tuomo Nikulainen; Antti-Jussi Tahvanainen; Matthias Deschryvere; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2009)
This paper aims to provide new insights into the analysis of National Innovation Systems (NIS). Whereas the common approach is to analyze specific parts or a defined set of actors and their interactions, this paper attempts to take a more systemic approach by analyzing results of 13 surveys directed to different sets of actors related to the Finnish NIS. The focus is on the overall complexity of the system, the demand- and user-based dimensions of innovative activities and policies, internationalisation of innovative activities, public support for high growth companies, regional innovation policies, and educational policies. The results are mostly descriptive and the emphasis is on the most important findings of the surveys. In addition to the main findings, the paper includes all questionnaires and a description of the complete data set.
Keywords: O30; O38; 330; National Innovation System; evaluation; Finland; survey; Innovation; Innovationspolitik; Bewertung; Finnland